Theoretical Basis for Primary School Education in the Process of Forming Schools - Sayidova Ziynat Yoqubovna (Zien Journals, 2022)
During the colonial era , the courage shown by the pilgrims in the formation of new schools, the textbooks they developed, publications, and articles were compiled regulations, their activities in fundamental reform of education
Keywords: Children; Hojai Sibyon; Examination; Teacher